Geochemistry of Engineered Nanoparticles (CdSe/ZnS Quantum Dots) in Surface Waters - Supiandi, N. Izyan; Domingos, Rute F.; Benedetti, Marc F.; Sivry, Yann (Frontiers in Environmental Science, 2020)
The difficulties when studying the behavior of engineered nanoparticles (ENPs), and the subsequent metal speciation in aquatic ecosystems, at concentrations relevant of environment (i.e. ppt level) are often related to the occurrence of ENPs constitutive elements at high concentrations as a background in aquatic media (i.e.). In this study, the physico-chemical behavior of CdSe/ZnS quantum dots (QDs) when spread at very low concentration in surface waters was investigated. The above-mentioned issues were overcome with the use of isotopically labeled QDs, separated by centrifugal ultrafiltration (CU) and measured by HR-ICP-MS, combined with the detection of free and labile metal ions by Scanned Stripping ChronoPotentiometry (SSCP). They firmly provided a thorough comprehension regarding the transformation of QDs in surface waters. The physicochemical conditions of the medium including the presence of an analogue of natural organic matter and a mineral (i.e. fulvic acid, goethite), the manufactured coating of the QDs (here thioglycolic acid), and the occurrence of added Zn in the medium, were considered in the study. The overall results show that, in the absence of mineral/organic matter, the TGA ligands in solution detached from the QDs surface after dissolution control the metal ions speciation, especially for Cd. Conversely in a more representative aquatic ecosystem conditions (i.e. with Zn in the background media together with fulvic acid and goethite), almost no Zn nor Cd dissolution from the QDs is detected. SSCP measurements reveal that the Zn complexes formed with the organic/mineral material in the system are inert, whereas the speciation model calculations indicated that Cd2+ is bound to TGA ligands in solution and organic/inorganic matter – therefore suggesting that, under the studied conditions, aquatic organisms will be exposed to a very low concentration of free and labile metal ions issued from the QDs.